Synthesis of biodiesel using the Mg/Al/Zn hydrotalcite/SBA-15 nanocomposite catalyst - Prabu, Marimuthu; Manikandan, Marimuthu; Kandasamy, Prabu; Kalaivani, P. R.; Rajendiran, Nagappan; Raja, Thirumalaiswamy (Acs Omega, 2019)
Biodiesel production is an enchanting and eccentric pathway for the reduction of use of fossil fuels and is procured from biologically available renewable sources such as oils and fats. A novel Mg/Al/Zn-based hydrotalcite/SBA-15 composite material having a high catalytic activity was developed and investigated for the transesterification of vegetable oil. The rationally developed composites were systematically characterized and assessed in the transesterification of soybean oil in the presence of methanol. The physicochemical evaluation of the nanocomposites demonstrated the influence of Zn in the textural characteristics, density of the basic sites, and successively the catalytic activity. The catalytic efficiency of the MAZ-x/SBA-15 composite could be linked with the basic site density determined by the temperature-programmed desorption of CO2. Among all the composites used, the MAZ-1/SBA-15 nanocomposite showed the highest activity for biodiesels, with a yield of around 90% under economical reaction conditions. The catalytic studies conferred that the fatty acid methyl ester yield is significantly influenced by various experimental conditions such as the catalyst molar ratio, reaction temperature, pressure, and contact time. It was also found that the incorporation of hydrotalcite into SBA-15 pore channels can enhance the catalyst efficiency and stability of the nanocomposite. Moreover, under mild reaction conditions, a remarkably stable catalytic performance was achieved for more than 200 h of time on stream with no catalyst deactivation.